STUDENT TEAM ACHIEVEMENT DIVISION (STAD) TECHNIQUE IN TEACHING READING COMPREHENSION - Mufidah, Ilma Anami (Lingua Scientia, 2013)
Â Abstract: Due to studentsâ problems and difficulties to learn English text, it is the teachersâ job to choose a suitable method in teaching reading comprehension. Student Team Achievement Division (STAD) is one method that is considered appropriate in making the students feel happy and enjoy their learning. When they are taught by using an enjoyable method, they will be able to enrich their reading comprehension easily and, in turn, they are expected to be able to master reading comprehension well. The problem and difficulties in learning reading comprehension were faced by the students at MTs Aswaja Tunggangri Kalidawir, and, thus, a study aimed at knowing the effectiveness of student team achievement division (STAD) technique in teaching reading comprehension was conducted in this school. The research design of this research was Pre-experimental design. The research finding in this research showed the difference between the averages of studentsâ score reading comprehension when they were taught without student team achievement division (STAD) technique (72,55 %) and when they were taught using student team achievement division (STAD) technique (77,6 %). Statistical calculation using T-test showed that the score of T count (10.254) was greater than that of T table (1.725) with significant level 5 % and degree of freedom of 32. It was concluded that student team achievement division (STAD) technique is an effective method in teaching reading comprehension to junior high school, especially for eight grade at MTs Aswaja Tunggangri Kalidawir.Â Keywords: STAD Technique, Reading Comprehension